Aqueous zinc ion battery electrolyte, battery and zinc negative electrode protection method thereof

By adding shikimic acid additives to the electrolyte of the aqueous zinc ion battery, the hydrogen bond network of the electrolyte is regulated, and the problems of zinc negative electrode corrosion and hydrogen evolution reaction are solved, which significantly improves the cycle life of the zinc negative electrode and the stability of the battery.

CN119480938AInactive Publication Date: 2025-02-18INNER MONGOLIA UNIV OF TECH

Patent Information

Application Number
CN202510066909.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the working process of the aqueous zinc ion battery, due to the growth and spontaneous corrosion of the dendrites on the negative electrode side, its long-term stability is poor, and the hydrogen evolution reaction is intensified, affecting the Coulomb efficiency of the zinc metal negative electrode.

Method used

By adding shikimic acid additives to the electrolyte of the aqueous zinc ion battery, the hydrogen bond network of the electrolyte is regulated, the zinc ion solvation structure is optimized, and the zinc negative electrode corrosion, hydrogen evolution reaction and dendrites are inhibited.

Benefits of technology

It effectively improves the cycle life of the zinc negative electrode, reduces the interface impedance, optimizes the deposition morphology, inhibits the formation of dendrites, and weakens the occurrence of hydrogen evolution reactions and side reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480938A_ABST
    Figure CN119480938A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of electrochemical energy storage, and particularly relates to a water-based zinc ion battery electrolyte, a battery and a zinc negative electrode protection method of the battery, zinc negative electrode corrosion, hydrogen evolution reaction and dendritic crystal growth are effectively inhibited by regulating and controlling the electrolyte, changing a hydrogen bond network of the electrolyte and optimizing a zinc ion solvation structure, and the cycle life of the zinc negative electrode is prolonged. The solvent of the electrolyte is water, and the solute is zinc sulfate and shikimic acid. When the prepared electrolyte is used for assembling the zinc symmetric battery, the interface impedance is obviously reduced, the deposition morphology is optimized, the formation of dendritic crystals is inhibited, hydrogen evolution reaction and side reaction are inhibited, and the cycle life of a zinc negative electrode can be effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electrochemical energy storage, relates to an aqueous zinc ion battery electrolyte containing shikimic acid and an application thereof, and specifically relates to an aqueous zinc ion battery electrolyte, a battery and a protection method for a zinc negative electrode thereof. Background Art

[0002] Compared with existing energy storage technologies (such as lithium-ion batteries and lead-acid batteries), aqueous batteries have advantages such as safety, economy, and environmental protection. Metallic zinc (Zn) has a good redox potential (-0.76 V vs. SHE) that matches the electrochemical stability window of water and a high capacity of 820 mAh g –1 (5854 mAh cm -3 ), which has led to the widespread development of aqueous zinc-ion batteries.

[0003] During the operation of aqueous zinc-ion batteries, the growth of dendrites on the negative electrode and the occurrence of spontaneous corrosion make their long-term stability poor. In the current mainstream weakly acidic electrolyte environment (ZnSO 4 、ZnCl、Zn(Otf) 2 etc.), due to the enhanced proton activity, Zn and H 2 The spontaneous corrosion process of O is accelerated, the hydrogen evolution reaction (HER) is intensified, and the OH generated at the negative electrode interface - Will be with Zn 2+ Further reaction produces insoluble Zn 4 (OH) 6 SO 4 ·xH 2 O, Zn(OH) 2 , ZnO and other corrosion products affect the Coulombic efficiency of the Zn metal anode.

[0004] Therefore, it is of great significance to find suitable additives to optimize the electrolyte of zinc-ion batteries, regulate the zinc ion transport at the negative electrode / electrolyte interface, inhibit zinc dendrites, hydrogen evolution and corrosion, and thus improve the electrochemical stability and cycle life of the zinc negative electrode. Summary of the invention

[0005] In view of this, the present invention discloses an aqueous zinc ion battery electrolyte, a battery and a method for protecting the zinc negative electrode thereof. By regulating the electrolyte, the hydrogen bond network of the electrolyte is changed, the zinc ion solvation structure is optimized, the zinc negative electrode corrosion, hydrogen evolution reaction and dendrite growth are effectively inhibited, and the cycle life of the zinc negative electrode is improved.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] The first technical purpose of the present invention is to provide a method for protecting the zinc negative electrode in a zinc ion battery. A shikimic acid additive is added to the electrolyte of the aqueous zinc ion battery, and the hydrogen bond network of the electrolyte is changed through electrolyte regulation, the zinc ion solvation structure is optimized, and the zinc negative electrode corrosion, hydrogen evolution reaction and dendrite growth are effectively inhibited, thereby improving the cycle life of the zinc negative electrode.

[0008] The second technical purpose of the present invention is to provide an aqueous zinc ion battery electrolyte, comprising: a soluble zinc salt, deionized water and the shikimic acid additive as described above; the concentration of the shikimic acid additive is 0.5-50 g L -1 , the preferred concentration is 5gL -1 .

[0009] Furthermore, the concentration of the soluble zinc salt in the aqueous zinc ion battery electrolyte is 1 mol / L.

[0010] Furthermore, the soluble zinc salt is zinc sulfate.

[0011] Furthermore, the preparation step of the aqueous zinc ion battery electrolyte is: dissolving zinc sulfate heptahydrate powder and shikimic acid powder in a certain amount of deionized water, and fixing the volume; the specific steps are as follows:

[0012] Use a beaker to add 10 mL of deionized water, add 5.751 g of zinc sulfate heptahydrate while stirring at medium speed, add 10-1000 mg of shikimic acid after it is completely dissolved, and after it is completely dissolved, introduce the prepared solution into a 20 mL volumetric flask to make up to volume to obtain 20 mL of aqueous zinc ion battery electrolyte. The above steps are all carried out at room temperature.

[0013] The third technical purpose of the present invention is to provide an aqueous zinc ion battery, which contains the aqueous zinc ion battery electrolyte added with shikimic acid as described above.

[0014] Furthermore, the aqueous zinc ion battery consists of a positive electrode, a negative electrode, a separator and the aqueous zinc ion battery electrolyte.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] The present invention changes the hydrogen bond network of the electrolyte through electrolyte regulation, optimizes the zinc ion solvation structure, effectively inhibits zinc negative electrode corrosion, hydrogen evolution reaction and dendrite growth, and improves the cycle life of the zinc negative electrode. The electrolyte solvent is water, and the solute is zinc sulfate and shikimic acid. When the prepared electrolyte is used to assemble a zinc symmetrical battery, the interface impedance is significantly reduced, the deposition morphology is optimized, the formation of dendrites is inhibited, and the hydrogen evolution reaction and side reactions are inhibited, which can effectively improve the cycle life of the zinc negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0018] Figure 1 This is a long cycle test diagram of the zinc symmetric battery in Implementation Example 1.

[0019] Figure 2 This is a long cycle test diagram of the zinc symmetric battery in Implementation Example 2.

[0020] Figure 3 This is a long cycle test diagram of the zinc symmetric battery in Implementation Example 3.

[0021] Figure 4 This is a long cycle test diagram of the zinc symmetric battery in Implementation Example 4.

[0022] Figure 5 This is a long cycle test diagram of the zinc symmetric battery in Implementation Example 5.

[0023] Figure 6 This is a SEM image of the surface of the zinc electrode sheet in Implementation Option 7.

[0024] Figure 7 This is a long cycle test diagram of the zinc symmetric battery in comparison scheme 1.

[0025] Figure 8 This is a long cycle test diagram of the zinc symmetric battery in comparison scheme 2.

[0026] Fig. 9 This is a long cycle test diagram of the zinc symmetric battery in comparison scheme 3.

[0027] Fig.10 This is a long cycle test diagram of the zinc symmetric battery in comparison scheme 4.

[0028] Fig.11 This is a comparison diagram of the AC impedance of the zinc symmetrical battery in Implementation Scheme 6 and Comparative Scheme 5.

[0029] Fig.12 This is the SEM image of the zinc electrode surface in Comparative Scheme 6.

[0030] Fig.13 Comparison of battery thickness before and after the cycle of implementation scheme 8.

[0031] Fig.14 Comparison of battery thickness before and after cycle for comparison scheme 7.

[0032] Fig.151M ZnSO 4 The electrolyte is between 2800 and 4000 cm -1 Raman spectra nearby.

[0033] Fig.16 1M ZnSO 4 + 5g L -1 Shikimic acid electrolyte at 2800~4000cm -1 Nearby Raman spectra. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] The word "embodiment" used here as an "exemplary" does not necessarily mean that any embodiment described is superior to or better than other embodiments. Unless otherwise specified, the performance index tests in the embodiments of this application are performed using conventional test methods in the art. It should be understood that the terms described in this application are only used to describe specific implementation methods and are not used to limit the content disclosed in this application.

[0036] Unless otherwise specified, the technical and scientific terms used in this document have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs; other experimental methods and technical means not specifically specified in this application refer to experimental methods and technical means commonly used by ordinary technicians in this field.

[0037] In order to better illustrate the content of the present application, numerous specific details are provided in the specific examples below. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In the embodiments, some methods, means, instruments, equipment, etc. well known to those skilled in the art are not described in detail in order to highlight the main purpose of the present application.

[0038] Under the premise of no conflict, the technical features disclosed in the embodiments of the present application can be combined arbitrarily, and the resulting technical solutions belong to the contents disclosed in the embodiments of the present application.

[0039] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as a limitation of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above invention content are also considered to fall within the protection scope of the present invention.

[0040] It should be noted that the equipment used in the following experimental process are: deionized water maker, magnetic stirrer, ultrasonic cleaner, drying box, battery testing system; the raw materials used are: zinc sulfate heptahydrate (Aladdin, 99.995% metalbasis), shikimic acid (Ron, 98%).

[0041] Implementation 1:

[0042] The specific implementation steps are as follows. The entire process is carried out at room temperature and pressure.

[0043] 1. Preparation of electrolyte

[0044] 1) Use a 50mL beaker to add 10mL of deionized water, stir at medium speed (about 300r / min) and add 5.751g of zinc sulfate heptahydrate until it is completely dissolved;

[0045] 2) Add 100 mg of shikimic acid and wait until it is completely dissolved;

[0046] 3) Add the solution prepared in 2) to a 20 mL volumetric flask to obtain 20 mL of 1 mol L -1 Zinc sulfate + 5g L -1 Shikimic acid solution.

[0047] 2. Electrode Preparation

[0048] Use 1000-mesh and 2000-mesh sandpaper to polish the 50-micron-thick zinc foil, cut it into discs with a diameter of 12 mm, use anhydrous ethanol to ultrasonically clean it for 20 minutes, and then dry it for use.

[0049] 3. Battery Assembly

[0050] The zinc foil was used as an electrode and the glass fiber filter membrane was used as a diaphragm. -1 Zinc sulfate + 5g L -1 The shikimic acid solution was used as the electrolyte and assembled into CR2032 batteries.

[0051] 4. Battery Test

[0052] Place the above battery in a battery tester and set the condition to 2.0 mA cm -2 , with a fixed charge and discharge capacity of 2 mAh cm -2 , and conduct long cycle performance test. The results are attached Figure 1 shown.

[0053] Implementation 2:

[0054] 1) Use a 50mL beaker to add 10mL of deionized water, stir at medium speed (about 300r / min) and add 5.751g of zinc sulfate heptahydrate until it is completely dissolved;

[0055] 2) Add 100 mg of shikimic acid and wait until it is completely dissolved;

[0056] 3) Add the solution prepared in 2) to a 20 mL volumetric flask to obtain 20 mL of 1 mol L -1 Zinc sulfate + 5g L -1 Shikimic acid solution.

[0057] 2. Electrode Preparation

[0058] Use 1000-mesh and 2000-mesh sandpaper to polish the 50-micron-thick zinc foil, cut it into discs with a diameter of 12 mm, use anhydrous ethanol to ultrasonically clean it for 20 minutes, and then dry it for use.

[0059] 3. Battery Assembly

[0060] The zinc foil was used as an electrode and the glass fiber filter membrane was used as a diaphragm. -1 Zinc sulfate + 5g L -1 The shikimic acid solution was used as the electrolyte and assembled into CR2032 batteries.

[0061] 4. Battery Test

[0062] Place the above battery in a battery tester and set the condition to 5.0 mA cm -2 , the fixed charge and discharge capacity is 2.0mAh cm -2 , and conduct long cycle performance tests.

[0063] Implementation 3:

[0064] 1) Use a 50mL beaker to add 10mL of deionized water, stir at medium speed (about 300r / min) and add 5.751g of zinc sulfate heptahydrate until it is completely dissolved;

[0065] 2) Add 100 mg of shikimic acid and wait until it is completely dissolved;

[0066] 3) Add the solution prepared in 2) to a 20 mL volumetric flask to obtain 20 mL of 1 mol L -1 Zinc sulfate + 5g L -1 Shikimic acid solution.

[0067] 2. Electrode Preparation

[0068] Use 1000-mesh and 2000-mesh sandpaper to polish the 50-micron-thick zinc foil, cut it into discs with a diameter of 12 mm, use anhydrous ethanol to ultrasonically clean it for 20 minutes, and then dry it for use.

[0069] 3. Battery Assembly

[0070] The zinc foil was used as an electrode and the glass fiber filter membrane was used as a diaphragm. -1 Zinc sulfate + 5g L -1 The shikimic acid solution was used as the electrolyte and assembled into CR2032 batteries.

[0071] 4. Battery Test

[0072] Place the above battery in a battery tester and set the condition to 10.0 mA cm -2 , the fixed charge and discharge capacity is 2.0mAh cm -2 , and conduct long cycle performance tests.

[0073] Implementation 4:

[0074] 1) Use a 50mL beaker to add 10mL of deionized water, stir at medium speed (about 300r / min) and add 5.751g of zinc sulfate heptahydrate until it is completely dissolved;

[0075] 2) Add 10 mg of shikimic acid and wait until it is completely dissolved;

[0076] 3) Add the solution prepared in 2) to a 20 mL volumetric flask to obtain 20 mL of 1 mol L -1 Zinc sulfate + 0.5 g L -1 Shikimic acid solution.

[0077] 2. Electrode Preparation

[0078] Use 1000-mesh and 2000-mesh sandpaper to polish the 50-micron-thick zinc foil, cut it into discs with a diameter of 12 mm, use anhydrous ethanol to ultrasonically clean it for 20 minutes, and then dry it for use.

[0079] 3. Battery Assembly

[0080] The zinc foil was used as an electrode and the glass fiber filter membrane was used as a diaphragm. -1 Zinc sulfate + 0.5 g L -1 The shikimic acid solution was used as the electrolyte and assembled into CR2032 batteries.

[0081] 4. Battery Test

[0082] Place the above battery in a battery tester and set the condition to 2.0 mA cm -2 , the fixed charge and discharge capacity is 2.0mAh cm -2 , and conduct long cycle performance tests.

[0083] Implementation 5:

[0084] 1) Use a 50mL beaker to add 10mL of deionized water, stir at medium speed (about 300r / min) and add 5.751g of zinc sulfate heptahydrate until it is completely dissolved;

[0085] 2) Add 1g of shikimic acid and wait for it to dissolve completely;

[0086] 3) Add the solution prepared in 2) to a 20 mL volumetric flask to obtain 20 mL of 1 mol L -1 Zinc sulfate + 50g L -1 Shikimic acid solution.

[0087] 2. Electrode Preparation

[0088] Use 1000-mesh and 2000-mesh sandpaper to polish the 50-micron-thick zinc foil, cut it into discs with a diameter of 12 mm, use anhydrous ethanol to ultrasonically clean it for 20 minutes, and then dry it for use.

[0089] 3. Battery Assembly

[0090] The zinc foil was used as an electrode and the glass fiber filter membrane was used as a diaphragm. -1 Zinc sulfate +50g L -1 The shikimic acid solution was used as the electrolyte and assembled into CR2032 batteries.

[0091] 4. Battery Test

[0092] Place the above battery in a battery tester and set the condition to 2.0 mA cm -2 , the fixed charge and discharge capacity is 2.0mAh cm -2 , and conduct long cycle performance tests.

[0093] Implementation 6:

[0094] The specific implementation steps are as follows, and the entire process is carried out at room temperature and normal pressure:

[0095] A zinc symmetrical battery was prepared using the method of Implementation Option 1. The battery was placed in an electrochemical workstation and left to stand for 2 hours. The amplitude was set to 5 mV and the range was 1000000~0.01 Hz to perform an AC impedance test.

[0096] Implementation 7:

[0097] The specific implementation steps are as follows, and the entire process is carried out at room temperature and normal pressure:

[0098] A zinc symmetrical battery was prepared using the method of Implementation Example 1. After 25 cycles, the battery was disassembled, and the surface of the electrode was rinsed clean with deionized water and alcohol. After drying, the surface morphology was observed using a scanning electron microscope.

[0099] Implementation 8:

[0100] The specific implementation steps are as follows, and the entire process is carried out at room temperature and normal pressure:

[0101] A zinc symmetric battery was prepared using the method of Embodiment 1, and its thickness was measured using a micrometer. The condition was then set to 5.0 mA cm -2 , the fixed charge and discharge capacity is 2.0mAh cm -2 , conduct long cycle performance test, and test its thickness again after 300 cycles.

[0102] In order to further demonstrate the beneficial effects of the present invention and to better understand the present invention, the following comparative examples are used to further illustrate the technical features disclosed in the present invention, but they should not be construed as limiting the present invention. Other improvements made by those skilled in the art based on the above invention content without inventive work are also considered to fall within the scope of protection of the present invention.

[0103] Comparison plan 1:

[0104] 1) Use a 50mL beaker to add 10mL of deionized water, stir at medium speed (about 300r / min) and add 5.751g of zinc sulfate heptahydrate until it is completely dissolved;

[0105] 2) Add the solution prepared in 1) to a 20 mL volumetric flask to obtain 20 mL of 1 mol L -1 Zinc sulfate solution.

[0106] 2. Electrode Preparation

[0107] Use 1000-mesh and 2000-mesh sandpaper to polish the 50-micron-thick zinc foil, cut it into discs with a diameter of 12 mm, use anhydrous ethanol to ultrasonically clean it for 20 minutes, and then dry it for use.

[0108] 3. Battery Assembly

[0109] The zinc foil was used as an electrode and the glass fiber filter membrane was used as a diaphragm. -1 Zinc sulfate solution is used as the electrolyte and assembled into CR2032 batteries.

[0110] 4. Battery Test

[0111] Place the above battery in a battery tester and set the condition to 2.0 mA cm -2 , the fixed charge and discharge capacity is 2.0mAh cm -2 , and conduct long cycle performance tests.

[0112] Comparison plan 2:

[0113] 1) Use a 50mL beaker to add 10mL of deionized water, stir at medium speed (about 300r / min) and add 5.751g of zinc sulfate heptahydrate until it is completely dissolved;

[0114] 2) Add the solution prepared in 1) to a 20 mL volumetric flask to obtain 20 mL of 1 mol L -1 Zinc sulfate solution.

[0115] 2. Electrode Preparation

[0116] Use 1000-mesh and 2000-mesh sandpaper to polish the 50-micron-thick zinc foil, cut it into discs with a diameter of 12 mm, use anhydrous ethanol to ultrasonically clean it for 20 minutes, and then dry it for use.

[0117] 3. Battery Assembly

[0118] The zinc foil was used as an electrode and the glass fiber filter membrane was used as a diaphragm. -1 Zinc sulfate solution is used as the electrolyte and assembled into CR2032 batteries.

[0119] 4. Battery Test

[0120] Place the above battery in a battery tester and set the condition to 5.0 mA cm -2 , the fixed charge and discharge capacity is 2.0mAh cm -2 , and conduct long cycle performance tests.

[0121] Comparison plan 3:

[0122] 1) Use a 50mL beaker to add 10mL of deionized water, stir at medium speed (about 300r / min) and add 5.751g of zinc sulfate heptahydrate until it is completely dissolved;

[0123] 2) Add the solution prepared in 1) to a 20 mL volumetric flask to obtain 20 mL of 1 mol L -1 Zinc sulfate solution.

[0124] 2. Electrode Preparation

[0125] Use 1000-mesh and 2000-mesh sandpaper to polish the 50-micron-thick zinc foil, cut it into discs with a diameter of 12 mm, use anhydrous ethanol to ultrasonically clean it for 20 minutes, and then dry it for use.

[0126] 3. Battery Assembly

[0127] The zinc foil was used as an electrode and the glass fiber filter membrane was used as a diaphragm. -1 Zinc sulfate solution is used as the electrolyte and assembled into CR2032 batteries.

[0128] 4. Battery Test

[0129] Place the above battery in a battery tester and set the condition to 10.0 mA cm -2 , the fixed charge and discharge capacity is 2.0mAh cm -2 , and conduct long cycle performance tests.

[0130] Comparison plan 4:

[0131] 1) Use a 50mL beaker to add 10mL of deionized water, stir at medium speed (about 300r / min) and add 5.751g of zinc sulfate heptahydrate until it is completely dissolved;

[0132] 2) Add 100 mg of creatine and wait for it to dissolve completely;

[0133] 3) Add the solution prepared in 2) to a 20 mL volumetric flask to obtain 20 mL of 1 mol L -1 Zinc sulfate + 5gL -1 Creatine solution.

[0134] 2. Electrode Preparation

[0135] Use 1000-mesh and 2000-mesh sandpaper to polish the 50-micron-thick zinc foil, cut it into discs with a diameter of 12 mm, use anhydrous ethanol to ultrasonically clean it for 20 minutes, and then dry it for use.

[0136] 3. Battery Assembly

[0137] The zinc foil was used as an electrode and the glass fiber filter membrane was used as a diaphragm. -1 Zinc sulfate + 5gL -1 Creatine solution is used as electrolyte and assembled into CR2032 batteries.

[0138] 4. Battery Test

[0139] Place the above battery in a battery tester and set the condition to 2.0 mA cm -2 , the fixed charge and discharge capacity is 2.0mAh cm -2 , and conduct long cycle performance tests.

[0140] Comparison plan 5:

[0141] The specific implementation steps are as follows, and the entire process is carried out at room temperature and normal pressure:

[0142] A zinc symmetrical battery was prepared using the method of Comparative Scheme 1. The battery was placed in an electrochemical workstation and left to stand for 2 hours. The amplitude was set to 5 mV and the range was 1000000~0.01 Hz for AC impedance testing.

[0143] Comparison plan 6:

[0144] The specific implementation steps are as follows, and the entire process is carried out at room temperature and normal pressure:

[0145] A zinc symmetrical battery was prepared using the method of Comparative Scheme 1. After 25 cycles, the battery was disassembled, and the surface of the electrode was rinsed clean with deionized water and alcohol. After drying, the surface morphology was observed using a scanning electron microscope.

[0146] Comparison plan 7:

[0147] The specific implementation steps are as follows, and the entire process is carried out at room temperature and normal pressure:

[0148] A zinc symmetric battery was prepared using the method of Comparative Scheme 1, and its thickness was measured using a micrometer. The conditions were then set to 5.0 mA cm -2 , the fixed charge and discharge capacity is 2.0mAh cm -2 , conduct long cycle performance test, and test its thickness again after 300 cycles.

[0149] In summary, the present invention aims at the problems existing in the mainstream 1molL-1 zinc sulfate electrolyte in the current research of aqueous zinc ion batteries, and introduces an effective shikimic acid additive using a simple method. It has been verified that after the introduction of the shikimic acid additive, the interface impedance of the zinc symmetric battery is significantly reduced. Scanning electron microscopy shows that the deposition morphology is optimized and the formation of dendrites is inhibited. The thickness of the battery before and after the cycle was measured, and the results also showed that the thickness change after the battery cycle was smaller after the introduction of the shikimic acid additive, which indirectly verifies the inhibition of the hydrogen evolution reaction. Raman spectroscopy shows that after the introduction of shikimic acid, OH representing free water bonds 3 The electrolyte with shikimic acid additive at 2 mA cm -2 , 5 mA cm -2 , 10 mA cm -2 Under three different surface densities, the surface capacity is maintained at 2 mAh cm -2 Tests of zinc symmetric batteries have proven that this method can effectively improve the cycle life of the zinc negative electrode.

[0150] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for protecting a zinc negative electrode in a zinc ion battery, characterized in that: By adding shikimic acid additives to the electrolyte of aqueous zinc-ion batteries, the hydrogen bond network of the electrolyte is changed through electrolyte regulation, the zinc ion solvation structure is optimized, and the corrosion, hydrogen evolution reaction and dendrite growth of the zinc negative electrode are effectively inhibited, thereby improving the cycle life of the zinc negative electrode.

2. An aqueous zinc ion battery electrolyte, characterized in that: include: Soluble zinc salt, deionized water and the shikimic acid additive according to claim 1; the concentration of the shikimic acid additive is 0.5-50 g L -1 .

3. The aqueous zinc ion battery electrolyte according to claim 2, characterized in that The concentration of the soluble zinc salt in the aqueous zinc ion battery electrolyte is 1 mol / L.

4. The aqueous zinc ion battery electrolyte according to claim 3, characterized in that The soluble zinc salt is zinc sulfate.

5. An aqueous zinc ion battery, characterized in that: The aqueous zinc ion battery contains the aqueous zinc ion battery electrolyte according to any one of claims 2 to 4.

6. The aqueous zinc ion battery according to claim 5, characterized in that: The aqueous zinc ion battery consists of a positive electrode, a negative electrode, a diaphragm and the aqueous zinc ion battery electrolyte.

Citation Information

Patent Citations

  • Synthesis method of active cross-linked bagasse xylan / golden camellia flower shikimate-g-NVP

    CN111560097A

  • Application of carboxylic ester compound as aqueous electrolyte additive, electrolyte containing additive and zinc ion battery

    CN116315158A

  • Electrolyte additive, electrolyte, aqueous zinc ion battery containing electrolyte and preparation method of aqueous zinc ion battery

    CN116683048A

  • Three-dimensional multi-stage zinc negative electrode plate, aqueous zinc ion battery electrolyte and aqueous zinc ion battery

    CN117637975A

  • Functional electrolyte additive for aqueous zinc ion battery

    CN118136981A

Cited By

  • Modified aqueous zinc battery negative electrode and preparation method thereof

    CN121983507A